Implementation of SOP in Handling Guest Luggage Arriving at the RC Bali Hotel - Giri , I Kadek Pradeyobi Ariana Surya; Seniartha, I Wayan; Sunarsa, I Wayan (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2024)
The purpose of this study was to determine the implementation of handling guest luggage arriving at The Ritz-Carlton Bali Hotel. The research method used is descriptive qualitative, namely where this data analysis technique compiles data obtained through interviews with the Guest Service Supervisor and also observations of bellman employees. Other data that supports the Final Project comes from literature, journal references, books, and articles about the front office department, especially in the bellman section. From the results of the study, it can be seen that there is still performance that needs to be considered in handling guest luggage arriving at The Ritz-Carlton Bali Hotel. The suggestion that can be given is that the Guest Service Supervisor should always monitor his subordinates to carry out the SOP that has been applied to the bellman section